2008
DOI: 10.1038/sj.mt.6300371
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Adrenal Catecholamine Secretion by In Vivo Gene Transfer and Manipulation of G Protein–coupled Receptor Kinase-2 Activity

Abstract: We recently reported that the upregulation of adrenal G protein-coupled receptor kinase-2 (GRK2) causes enhanced catecholamine (CA) secretion by desensitizing sympatho-inhibitory alpha (2)-adrenergic receptors (alpha (2)ARs) of chromaffin cells, and thereby aggravating heart failure (HF). In this study, we sought to develop an efficient and reproducible in vivo adrenal gene transfer method to determine whether manipulation of adrenal GRK2 levels/activity regulates physiological CA secretion in rats. We specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
68
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 78 publications
(71 citation statements)
references
References 22 publications
2
68
0
1
Order By: Relevance
“…The hypothesis that GRK2 modulates chromaffin catecholamine secretion was further supported by experiments with adenoviral-mediated overexpression of GRK2 in rats as this caused an increase of plasma catecholamine levels. 31 Thus, elevated GRK2 expression levels and activity in the adrenal medulla appear to contribute greatly to plasma catecholamine elevation in HF, which certainly perpetuates the vicious SNS overdrive cycle in HF. 3,32 PHARMACOLOGICAL VERSUS GENE THERAPY STRATEGIES TARGETING ADRENERGIC SIGNALING IN HF Ideally, HF therapy would be designed to tackle the root of the underlying molecular signaling alterations and aimed at halting or reversing disease progression.…”
Section: Grk2: a Nodal Culprit In Hf Grk2 And The Cardiomyocytementioning
confidence: 99%
See 4 more Smart Citations
“…The hypothesis that GRK2 modulates chromaffin catecholamine secretion was further supported by experiments with adenoviral-mediated overexpression of GRK2 in rats as this caused an increase of plasma catecholamine levels. 31 Thus, elevated GRK2 expression levels and activity in the adrenal medulla appear to contribute greatly to plasma catecholamine elevation in HF, which certainly perpetuates the vicious SNS overdrive cycle in HF. 3,32 PHARMACOLOGICAL VERSUS GENE THERAPY STRATEGIES TARGETING ADRENERGIC SIGNALING IN HF Ideally, HF therapy would be designed to tackle the root of the underlying molecular signaling alterations and aimed at halting or reversing disease progression.…”
Section: Grk2: a Nodal Culprit In Hf Grk2 And The Cardiomyocytementioning
confidence: 99%
“…Most studies-including studies with bARKct expression in HF pigs-have shown a reversal of bAR dysfunction including receptor upregulation and a normalization of signaling; however, no doubt, there are effects of the bARKct that go beyond resensitization of cardiac bARs and these effects are currently being explored by us and others. 54,55 Adrenal GRK2 as a novel HF gene therapy target As discussed above, HF is associated with enhanced catecholamine secretion from the adrenal glands because of a 2c AR desensitization by GRK2. This central role in the critical elevation of plasma catecholamine levels contributing to HF development and progression renders adrenal GRK2 an interesting target for HF treatment.…”
Section: Targeting Grk2 By Gene Therapy For Hf J Reinkober Et Almentioning
confidence: 99%
See 3 more Smart Citations